Literacy Crisis: Health Education to Increase Public Awareness of Clinical Communication in the Digital Age - Mahmudah, Winda Woro; Santoso, Ronggo (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The background of this study began with the low level of health literacy, which has an impact on patients' understanding of technical terms during medical consultations. With the rapid development of information technology, people now find it easier to access various health information through digital media but are also faced with challenges related to filtering accurate and reliable information. Health education is an important factor in guiding people to understand and implement a healthy lifestyle based on correct information. Therefore, this study aims to analyze the role of health education in increasing public awareness of clinical communication in the digital era. In addition, it examines the phenomenon of patient confusion regarding medical terminology in clinical communication practices. Using a qualitative descriptive approach, researchers conducted in-depth interviews with eight patients aged 25–60 years, all of whom did not have a medical education background. The Wami Jaya Health Center in Nabire Regency conducted this study. Data were analyzed thematically. The results of the study showed that, although most people are used to accessing health information online, there are still gaps in understanding and implementing appropriate clinical communication. Therefore, health education programs that utilize digital technology, such as webinars, health applications, and interactive educational content, can be an effective solution to increase public awareness and knowledge about clinical communication. In addition, the research findings revealed four main patterns: lack of understanding of medical terms, passive communication behavior, linguistic gaps between doctors and patients, and ineffectiveness of written educational materials. This study concludes that the health literacy crisis is not just an individual problem but also a reflection of an unresponsive communication system.